2012
DOI: 10.1149/2.016302jss
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Non-Cd Quantum Dot Development for Lighting Applications

Abstract: During the past few years there has been a significant progress in adapting the properties of non-Cd quantum dots (QDs) for lighting applications. It includes synthesis of novel materials, improvement of quantum efficiency and thermal stability, and most importantly, manufacturability on a scale large enough to meet the needs of the lighting industry. In this paper, we review the characteristics of three most mature non-Cd QD material systems, InP, CuInS2 and doped ZnS/ZnSe, from the perspective of lighting ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 94 publications
1
65
0
1
Order By: Relevance
“…42 For semiconductor materials studied in the present study, the energy band gaps of bulk materials and optical bowing parameter have already been determined experimentally. 42 The effective masses of electrons and holes, m e * /m 0 and m h * /m 0 , for the unalloyed compounds have also reported in the previous papers; 8,[43][44][45][46][47][48][49] however, the values for intermediate compositions of the alloys have not yet been reported. Therefore, in the present calculation, the effective mass of alloys was assumed to be a mole fraction weighted mean effective mass of the two unalloyed compounds as a first approximation; for the AB x C 1 x pseudobinary alloys, the effective mass of the alloy at the composition x is expressed by the following equation:…”
Section: Calculationsmentioning
confidence: 64%
See 3 more Smart Citations
“…42 For semiconductor materials studied in the present study, the energy band gaps of bulk materials and optical bowing parameter have already been determined experimentally. 42 The effective masses of electrons and holes, m e * /m 0 and m h * /m 0 , for the unalloyed compounds have also reported in the previous papers; 8,[43][44][45][46][47][48][49] however, the values for intermediate compositions of the alloys have not yet been reported. Therefore, in the present calculation, the effective mass of alloys was assumed to be a mole fraction weighted mean effective mass of the two unalloyed compounds as a first approximation; for the AB x C 1 x pseudobinary alloys, the effective mass of the alloy at the composition x is expressed by the following equation:…”
Section: Calculationsmentioning
confidence: 64%
“…The parameters for the unalloyed bulk materials used in the present calculations are summarized in Table I. 8,29,32,43,[46][47][48][49][50][51][52][53][54] …”
Section: Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…InP [9], [10] and CuInS 2 [11], [12] QDs were found to exhibit high PL-QYs and luminance performance for the corresponding QLEDs by optimizing synthesis conditions, such as the synthesis temperature, the reaction time, the concentration of raw materials, and the insertion of a carrier blocking layer. Previous papers demonstrated that PL-QYs of more than 80% were achieved, and this value is high enough for practical display and biological applications [13], [14]. Furthermore, the luminance performance of QLEDs with Cd-free QDs has been improved by controlling the organic ligand [15]; however, further investigation is required due to insufficient understanding of carrier dynamics in QLEDs.…”
Section: Introductionmentioning
confidence: 99%